POTENSI BAHAYA LONGSOR LERENG PERBUKITAN LUBUK PARAKU KECAMATAN IX KOTO KABUPATEN DHARMASRAYA - Rozi, Fakhrur - (STKIP PGRI Sumbar, 2014)
The background of this research is a state of Lubuk Paraku hillsides area that was formerly natural forest grow quite lush now even plantations and cultivation even some residents building on the land. This study aims to describe the characteristics of land on the slopes of the hills Lubuk Paraku Dharmasraya subdistrict IX Koto, the potential avalanche danger hillsides Lubuk Paraku subdistrict IX Koto district Dharmasraya. The research is a descriptive through the processing and analysis of data in the form of primary data and secondary data. The primary data obtained through field measurements and laboratory analysis while the secondary data and rainfall data in the form of data maps, such as maps of slope, land use maps, topographic maps, soil type maps, geological maps then overlaid into land units map.Of overlay maps produced 14 units of land area of research and retrieval of sample points based on purposive sampling technique resulted in three research areas. The results of the study explained that the study site has an dedudasional landform, level of avalanche danger in the area of research, there is one criterion that is currently contained in land units D2.V.Pod.Ht.Pb, D2.V.Nit.Ht.Pb, D2.IV , Pod.Sb.Pb.